For Better or for Worse: Economic Positions of the Rich and the Poor: 1985-1995 - Olli Kangas (Luxembourg Income Study (LIS), 2001)
In the first section of the study, we analyze the cross-sectional relationship between poverty rates and the income level of the poor. Thereafter, we take a close look at changes in time: how poverty and 'richness' rates and changes in the income of the poor and the rich are related to each other. The second part of the paper illustrates how the economic tide has improved the lot of the middle-income earners, the worse-off and the best-off. Have the rich taken all the money and run? Is there anything left for the poor? The last section of the paper discusses the fairness of income distribution and presents some tasks for future research on the topics.
Keywords: 330; Armut; Einkommensverteilung; Rawls-Gerechtigkeitstheorie; OECD-Staaten